PENGARUH KEBIJAKAN PENYERTAAN MODAL DAERAH TERHADAP PELAYANAN PDAM TIRTA INDRAGIRI DI TEMBILAHAN - Oktaria Nita; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to analyze the influence of local government capital investment policy toward water supply company (pdam) services in tembilahan. The formulation of problem in this thesis is How the Influence of Local Goverment Capital Investment Policy Toward Water Supply Company (PDAM) Tirta Indragiri Services. The purpose of this research is in order to know about is there any influence of capital investment toward PDAM services, how much influence of capital investment toward PDAM services in Tembilahan, and how the influence of capital investment toward PDAM Tirta Indragiri services in Tembilahan. This research indicates that there is a positive and significant influence between capital investment and PDAM services in Tembilahan It means there is a releationship between capital investment variable (X) and PDAM services variable (Y).Keywords: Capital Investment, Local Government, and PDAM Tirta Indragiri services